2006
DOI: 10.1002/anie.200603013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Waterwheel (Noria) from a Simple Condensation of Resorcinol and an Alkanedial

Abstract: A wheel surprise: Reaction of resorcinol and 1,5‐pentanedial in ethanol at 80 °C for 48 h in the presence of HCl surprisingly afforded a soluble cyclic oligomer in high yield (83 %) under thermodynamic control. Single‐crystal X‐ray analysis revealed a waterwheel‐like structure with a large hydrophobic hole through the center (see picture). A carboxylic ester derivative of the compound was shown to be highly selective for Rb+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(80 citation statements)
references
References 23 publications
2
75
0
2
Order By: Relevance
“…Figure 1 shows Resists 1-4, which were based on noria. 6 Resists 1 and 2 were prepared from noria derivatives with pendant adamantyl ester (AD) and cyclohexyl 2-propyl ether moieties, whose degrees of protecting groups (DP) were 40 and 23%, respectively.…”
Section: Synthesis Of Resist Materials 1-8mentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows Resists 1-4, which were based on noria. 6 Resists 1 and 2 were prepared from noria derivatives with pendant adamantyl ester (AD) and cyclohexyl 2-propyl ether moieties, whose degrees of protecting groups (DP) were 40 and 23%, respectively.…”
Section: Synthesis Of Resist Materials 1-8mentioning
confidence: 99%
“…Recently, Kudo and co-workers succeeded in the synthesis of a new ladder cyclic oligomer "noria" (water wheel in Latin) 6 and reported the synthesis and photochemical reactivity of noria derivatives containing t-butoxycarbonyl groups, 7,8 t-butylester groups, 9 acetal groups, 10,11 and adamantyl ester groups. [12][13][14][15] It was found that these noria derivatives had high photo-reactivity and produced clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using EUV exposure tool, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kudo and coworkers have succeeded in the synthesis of a new ladder cyclic oligomer "noria" (water wheel in Latin) [13] and reported the synthesis and photochemical reactivity of noria derivatives containing t-butoxycarbonyl groups [14,15], t-butylester groups [16], acetal groups [17,18], and adamantyl ester groups [19][20][21][22][23]. It was found that these noria derivatives have high photoreactivity and produce clear line and space patterns with resolutions of 50-70 nm using an EB exposure tool and 26 nm using an EUV exposure tool [15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, the development of superior photo-resist materials have been required. We also have been investigated to offer higher resolution resist pattern based on ladder cyclic oligomer "noria" (noria = water wheel in Latin) [3]. The synthesis, physical properties, and patterning properties of noria derivatives with pendant t-butyl ester groups [4], t-butyloxycarbonyl groups [5], adamantyl ester groups [6 -8], and cyclohexyl acetal moieties [9], and oxetanyl groups [10] using EB and EUV exposure system.…”
Section: Introductionmentioning
confidence: 99%